COVID-19 pandemic and vitamin D: rising trends in status and in daily amounts of vitamin D provided by supplements - Patrick J Twomey; Malachi J McKenna; Rachel K Crowley; Oonagh C Lyons; Mary AT Flynn; Mark T Kilbane (BMJ Open, 2022)
Objectives Since the onset of the COVID-19 pandemic in 2020, there have been plausible suggestions about the need to augment vitamin D intake by supplementation in order to prevent SARS-CoV2 infection and reduce mortality. Some groups have advocated supplementation for all adults, but governmental agencies have advocated targeted supplementation. We sought to explore the effect of the COVID-19 pandemic on both vitamin D status and on the dose of new-to-market vitamin D supplements.Setting University hospital, Dublin, Ireland.Participants Laboratory-based samples of circulating 25-hydroxyvitamin D (25OHD) (n=100 505).Primary and secondary outcome measures Primary outcomes: comparing yearly average 25OHD prior to the pandemic (April 2019 to March 2020) with during the pandemic (April 2020 to March 2021) and comparing the dose of new-to-market vitamin D supplements between 2017 and 2021 (n=2689). Secondary outcome: comparing prevalence of vitamin D deficiency and vitamin D excess during the two time periods.Results The average yearly serum 25OHD measurement increased by 2.8 nmol/L (61.4, 95% CI 61.5 to 61.7 vs 58.6, 95% CI 58.4 to 58.9, p<0.001), which was almost threefold higher than two similar trend analyses that we conducted between 1993 and 2016. There was a lower prevalence of low 25OHD and a higher prevalence of high 25OHD. The dose of new-to-market vitamin D supplements was higher in the years 2020–2021 compared with the years 2017–2019 (p<0.001).Conclusions We showed significant increases in serum 25OHD and in the dose of new-to-market vitamin D supplements. The frequency of low vitamin D status reduced indicating benefit, but the frequency of vitamin D excess increased indicating risk of harm. Rather than a blanket recommendation about vitamin D supplementation for all adults, we recommend a targeted approach of supplementation within current governmental guidelines to at-risk groups and cautioning consumers about adverse effects of high dose supplements on the market.